Population and development: impacts on environmental performance. Issue 3 (2nd July 2016) - Jain, Prerna; Jain, Pragati
ABSTRACT: Population growth and development patterns have a significant impact on the environmental performance. The issue of concern is whether population growth or the consumption/production patterns are responsible for environmental deterioration. This paper is an attempt to capture the impact of technological development, affluence, and population on environmental performance index, while previous studies had captured the impact of these three factors on environment only through CO2 emissions. The analysis reveals that technological development and population size have a negative impact on environmental performance, whereas measures to improve affluence have a positive impact. Technological development has increased the production of energy efficient products but at the same time consumption of these products has increased manifold leading to environmental deterioration. Demographic attributes need specific attention to improve environmental performance. This paper concludes on some policy reflections on slowing the population growth as well as persuades individuals and economies to relook to their consumption and production patterns and channelize their efforts to protect the environment.